2004
DOI: 10.1038/sj.ijo.0802803
|View full text |Cite
|
Sign up to set email alerts
|

Gene–gene interaction between PPARγ2 and ADRβ3 increases obesity risk in children and adolescents

Abstract: AIMS:Multiple genes are likely to be involved in obesity and these genes may interact with environmental factors to influence obesity risk. Our aim was to explore the synergistic contribution of the two polymorphisms: Pro12Ala of the PPARg2 gene and Trp64Arg of the ADRb3 gene to obesity risk in a Spanish children and adolescent population. METHODS: We designed a sex-and age-matched case-control study. Participants were 185 obese and 185 control children (aged 5-18 y) from the Navarra region, recruited through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 24 publications
6
50
1
1
Order By: Relevance
“…There is growing evidence that gene-gene interactions are important contributors to genetic variation in complex human diseases. [1][2][3][4][5][6] However, detecting gene-gene interactions remains a challenge due to the lack of powerful statistical methods. The most commonly used statistical approach for studying gene-gene interactions is to use a regression framework in which a pair of markers and their interaction terms are included as predictors.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that gene-gene interactions are important contributors to genetic variation in complex human diseases. [1][2][3][4][5][6] However, detecting gene-gene interactions remains a challenge due to the lack of powerful statistical methods. The most commonly used statistical approach for studying gene-gene interactions is to use a regression framework in which a pair of markers and their interaction terms are included as predictors.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,14,[30][31][32][33][34] In this regard, the current study showed that LPL Ser447Stop polymorphism, despite its functional role in promoting increases in LPL and the attendant lipid storage in adipocyte, 17,35 beneficially modified the association between obesity and the ADRB1 Arg389Gly polymorphism, particularly in white subjects. In the total sample, interactions between the two polymorphisms were significant in adulthood and for the longitudinal change.…”
Section: Discussionmentioning
confidence: 61%
“…These include the ADRA2B, 18,19 ADRB1, 20,21 ADRB2 18,22-29 and ADRB3 genes. 18,19,28,30,31 Remarkably, most clinically effective antipsychotic drugs are potent ADRA1 antagonists. 32 A possible role of the ADRA1A promoter region in the development of schizophrenia was found in an isolated Spanish population, 33 but not in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%